## 共享

x+15-y=0

x-y=-15

4x-y=0

x-y=-15,4x-y=0

x-y=-15

x=y-15

4\left(y-15\right)-y=0

4y-60-y=0
4 乘上 y-15。
3y-60=0

3y=60

y=20

x=20-15

x=5

x=5,y=20

x+15-y=0

x-y=-15

4x-y=0

x-y=-15,4x-y=0

\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-15\\0\end{matrix}\right)

inverse(\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right))\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right))\left(\begin{matrix}-15\\0\end{matrix}\right)

\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right))\left(\begin{matrix}-15\\0\end{matrix}\right)

\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\4&-1\end{matrix}\right))\left(\begin{matrix}-15\\0\end{matrix}\right)

\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{-1-\left(-4\right)}&-\frac{-1}{-1-\left(-4\right)}\\-\frac{4}{-1-\left(-4\right)}&\frac{1}{-1-\left(-4\right)}\end{matrix}\right)\left(\begin{matrix}-15\\0\end{matrix}\right)

\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{3}&\frac{1}{3}\\-\frac{4}{3}&\frac{1}{3}\end{matrix}\right)\left(\begin{matrix}-15\\0\end{matrix}\right)

\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{3}\left(-15\right)\\-\frac{4}{3}\left(-15\right)\end{matrix}\right)

\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}5\\20\end{matrix}\right)

x=5,y=20

x+15-y=0

x-y=-15

4x-y=0

x-y=-15,4x-y=0

x-4x-y+y=-15

x-4x=-15

-3x=-15

x=5

4\times 5-y=0

20-y=0
4 乘上 5。
-y=-20

y=20

x=5,y=20